Characteristics of PCDD/Fs and metals in surface soil around an iron and steel plant in North China Plain. (February 2019) - Zhou, Tian; Bo, Xin; Qu, Jiabao; Wang, Longfei; Zhou, Jun; Li, Shibei
Abstract: In this study, the level of 18 species of metals and 17 species of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) were monitored in surface soil samples around an iron and steel plant in the North China Plain. The concentration of PCDD/Fs and metals in the soil ranged from 0.16 to 4.5 ng I-TEQ/kg and 1.2 to 24, 182.2 mg/kg, respectively. Furthermore, the prevailing winds were confirmed to influence the spatial distribution of PCDD/Fs and metals concentrations. The highest concentration of PCDD/Fs was located in downwind soil sample 4 (S4), which showed more than 50% of PCDFs in the total PCDD/Fs, and high levels of lower chlorinated PCDFs. Moreover, the highest Cd and Zn concentrations of 18.1 and 2647.8 mg/kg, respectively, were observed in soil collected from S4, which were significantly above the government guidelines for metals in farmland soil. Our results show that a group of metals (Mg, Al, K, Fe, Cu, Zn, Se, Cd, Sb and Pb) was well correlated with all PCDD/Fs except three (OCDD, 1, 2, 3, 4, 6, 7, 8-HpCDD and 1, 2, 3, 7, 8, 9-HxCDD), which likely originated from iron and steel processes. Additionally, Pb, Zn, Cd and all polychlorinated dibenzofurans showed a good correlation and grouped in one cluster, suggesting anthropogenic sources from sintering process. Therefore, the metallic characteristics in soil, especially the Pb, Zn and Cd tracers, implied evidence of the accumulation of PCDD/Fs from sinter plants. Highlights: PCDD/Fs pollution from iron and steel plants in north China is a serious problem. Soil heavy metals fingerprints indicated dioxin levels around iron and steel plants. High PCDD/Fs, Cd, Zn, and Pb levels were detected in downwind soil.